Production Enhancement Technology of Pegagan (Centella asiatica) - Noverita Sprinse Vinolina; Marline Nainggolan; Rolan Siregar (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2018)
Centella asiatica has long been known as one of medicinal plants. Profound study is needed to be able to find out the responses of Pegagan to various treatments in order to increase centelloside content. It was also previously reported that the highest asiaticoside content was found at the lowland pegagan, Pantai Labu. Current study on planted lowland pegagan of Deli Serdang with 2.38% of asiaticoside content was aimed to know the response of the plants to phosphorus fertilizing, elicitorand harvesting time related to biomass production from leaves, petioles, roots and tendrils. Phosphorus fertilizer was applied in four levels: 0, 18, 36 and 54 kg P2O5.ha-1, which affected centelloside synthesis, and elicitor of methyl jasmonate was given at three levels: 0, 100, 200 μM, while harvesting time was set up at 56, 70 and 84 days after planting (DAP). Data showed that the best combination for biomass production was obtained when there was no elicitor and harvesting was done at 84 DAP. The best combination between methyl jasmonate hormone and harvesting period in both fresh weight of leaves and petioles as well as roots was obtained when there was no hormone and harvesting time was 84 days old.